Photon scattering by an atomic ensemble coupled to a one-dimensional nanophotonic waveguide - Song, Guo-Zhu (2018)
We theoretically investigate the quantum scattering of a weak coherent input field interacting with an ensemble of Λ-type three-level atoms coupled to a one-dimensional waveguide. With an effective non-Hermitian Hamiltonian, we study the collective interaction between the atoms mediated by the waveguide mode. In our scheme, the atoms are randomly placed in the lattice along the axis of the one-dimensional waveguide. Many interesting optical properties occur in our waveguide-atom system, such as electromagnetically induced transparency. We quantify the influence of decoherence originating from both dephasing and population relaxation, and analyze the effect of the inhomogeneous broadening on the transport properties of the incident field. Moreover, we observe that strong photon-photon correlation with quantum beats can be generated in the off-resonant case, which provides an effective method for producing nonclassical light in experiment. With remarkable progress in waveguide-emitter systems, our scheme may be experimentally feasible in the near future.